Hubungan Coping Stress dan Kecerdasan Inteligensi dengan Prestasi Akademik Taruna Tingkat II Akademi Militer Magelang - Dinarsih, Mustika Dwi; , Dr. Nisa Rachmah N.A., M.Si.,Psi (2017)
The Academic achievement is result from learning who make changes to mind, feeling, and behavior. One way to improve academic achievement with a good coping stress and ellectual intelligence. This study aims to determine the relationship of stress coping and intellectual Intelligence with academic achievement of second level cadets of Magelang litaryAcademy either partially or simultaneously. Subject in this study were 200 of second level cadets of Magelang Military cademy. This reseach method using cluster random sampling. Methods of data collection using a scale coping stress, result of psychological test, and result of semester exams of second level cadets of Magelang Military Academy. Data analysis techniqus usingpartial correlation test and regression analysis. The results showed that Coping Stress has a significant relationship with Academic Achievement, where the relationship is negative which means lower Coping stress will lead to increased academic achievement. Intellectual Intelligence has a significant relationship with Academic Achievement, where the relationship is positive which means the higher Intellectual Intelligence will lead to academic achievement is increasing and the results show that together the relationship between coping stress and intelligence intelligence significantly related to academic achievement Taruna Level II Military Academy of Magelang. The onclusion of this research is coping stress and intelectual telligence become predictor of academic achievement of second level cadets of Magelang Military Academy. In accordaance has been applied by the Military Academy of Magelang, which improve his performance on the agenda held in an entertaiment that make the cadets become more creative and innovative. So that in accordance goal is to make cadets into leader who has knowledge, skills, personality, integrity, and has a national insight.